Altered Levels of Serum Zinc and Cadmium in Patients with Chronic Vesiculobullous Hand and Feet Dermatitis - Swastika Suvirya; Alpna Thakur; S. S. Pandey; S. K. Tripathi; Durgesh Kumar Dwivedi (Hindawi Limited, 2016)
Micronutrients serve many important functions in our body and altered levels of heavy and trace metals are associated with cutaneous and systemic disorders. Vesicular palmoplantar eczema is an entity whose etiopathogenesis is a mystery. In this prospective case-noncase study blood levels of Zinc and Cadmium in 37 patients of chronic vesiculobullous hand dermatitis were estimated and compared with 40 noncases with similar age and gender distributions. Low serum Zinc levels were found in patients as compared to noncases. The mean difference of serum Zinc between the case and noncase groups was 27.26; the mean value of serum Zinc between the two groups was statistically significant (p<0.0001). However, elevated Cadmium levels were detected in only 5 patients and in none of the noncases. The mean concentration of serum Cadmium was 2.32±0.38 μg/dL, with a range of 1.90-2.80 μg/dL for the five cases in whom Cadmium was detected. Various toxic and trace metals can interact by influencing each other's absorption, retention, distribution, and bioavailability in the body. The clinical significance of this finding lies in the possible beneficial role of Zinc supplementation in the therapy of chronic vesiculobullous hand dermatitis.